A Legal Analysis of Judges' Decisions as a Result of the Law Decree of the TNI Commander (Case Study of Surabaya PTUN Decision No. 124/G/2014/PTUN.SBY) - Suwardi, Suwardi; Leonardo Leba, Julio (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
This study examines the legal consequences of the Decree of the TNI Commander regarding land ownership disputes in Lidah Kulon Village, Surabaya, as addressed in Decision No. 124/G/2014/PTUN.SBY. The case involves claims from 156 individuals asserting ownership over 8.5 hectares of land, initially granted for TNI-AL members. The research highlights legal complexities arising from conflicting decrees, including Skep/29/IV/1993, and subsequent agreements involving PT. Ciputra Graha Prima Surabaya. Using normative legal research methods, this study analyzes the judicial considerations, ratio decidendi, and procedural limitations in the State Administrative Court (PTUN). The findings reveal that the object of the lawsuit does not fulfill the criteria of a concrete, individual, and final State Administrative Decision as defined by Indonesian law, leading to its inadmissibility (Niet Ontvankelijk verklaard). This research underscores the importance of transparency and adherence to legal frameworks in resolving administrative disputes involving state agencies and individual rights.